Soroprevalência de dengue em crianças e adolescentes no Distrito Sanitário Norte, Goiânia, Goiás, 2015 - Siqueira, Claudio Morais (2016)
Dengue is a viral acute febrile disease, considered today the most important arbovirus in the world due to their impact on morbidity, mortality and economy of the countries. Population serosurveys have been conducted worldwide and in Brazil for a better understanding of dengue transmission dynamics. These studies are also usefull to quantify prevalence rates and compare them to the information obtained by epidemiological surveillance of particular sites. Objective: determine the baseline serological profile for a cohort of children/adolescents between 2 and 16 years of age in the city of Goiânia, Goiás, in 2015. Methods: a cross-sectional study was conducted to assess the prevalence of dengue in the study group. We used the enzyme immunoassay for detection of IgG antibodies (ELISA IgG). Results: the overall prevalence of dengue virus (DENV) infection in children/adolescents was 38.3%. There was a significant increase in the seroprevalence according to age, ranging from 30.0% (95%CI 25.9-34.1) and 59.7% (95%CI 54.1%-65.3) in the groups between 5 to 9 and 14 to 16 years of age, respectively. In the multivariate model, age and a reported history of dengue were associated with a previous dengue infection. There was also an increase in the positive predictive value (PPV) of a reported history of dengue according to age. Conclusions: the increase in seroprevalence according to age observed in our study is expected in scenarios with endemic occurrence of infectious diseases. The increase in PPV is also expected, since infection by DENV tends to be more symptomatic in adolescents and adults compared to children. The understanding of dengue transmission dynamics is essential for evidence-based decisions. The establishment of a prospective cohort of children and adolescents in the city of Goiania associated with these baseline results will allow a comprehensive evaluation of the incidence of DENV infections in one of the most affected areas in Brazil.